Factors Influencing Philippines Tourist’ Revisit Intention: The Role and Effect of Destination Image, Tourist Experience, Perceived Value, and Tourist Satisfaction - Angelo Libre; Aldaba Manalo; Grida Saktian Laksito (International Journal of Quantitative Research and Modeling, 2022)
The Philippines is an agrarian-based tourism country, millions of tourists come to visit every year. However, most of the first-time visitors leave the question of why so few people decide to return for a tour of the Philippines' tourist destinations. This study aims to determine how the influence of the image of the destination, the experience of tourists on the intention to revisit through the value received and the satisfaction of tourists at tourist destinations in the Philippines. The research method used is quantitative, the sampling technique uses non-probability sampling and a sample of 287 respondents is obtained, the analytical tool used is Path Analysis and the hypothesis uses a significance test using SEM AMOS and SPSS analysis tools. The results of this study indicate that direct testing of the tourist experience variable affects revisit intention in tourist destinations in Philippines, then for direct testing the perceived value variable has a significant effect on tourist satisfaction at tourist destinations in the Philippines, then tourist satisfaction is able to mediate the relationship between tourist experience and revisit intention.